2014
DOI: 10.1016/j.jrras.2013.12.007
|View full text |Cite
|
Sign up to set email alerts
|

Effects of gamma irradiation on the development and reproduction of the greasy cutworm, Agrotis ipsilon (Hufn.)

Abstract: a b s t r a c tThree substerilizing doses 50, 100 and 150 Gy of gamma radiation were tested against full e grown male and female pupae or against full-grown male or female pupae of Agrotis ipsilon.The results showed that fecundity of irradiated females crossed with irradiated males was decreased by increasing irradiation dose. The decrease in egg e hatchability % and increase in sterility % induced by gamma radiation were found to be positively correlated with the dose level. The parentage of larval and pupal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 9 publications
1
10
0
2
Order By: Relevance
“…The sex ratio of the emerging F 1 adults was also in favor of males, and more males were obtained than in P and controls. The aforementioned incidents were similarly reported by Ibrahim (2012) on Spodoptera littoralis and Salem et al (2014) on Agrotis ipsilon.…”
Section: Discussionsupporting
confidence: 72%
“…The sex ratio of the emerging F 1 adults was also in favor of males, and more males were obtained than in P and controls. The aforementioned incidents were similarly reported by Ibrahim (2012) on Spodoptera littoralis and Salem et al (2014) on Agrotis ipsilon.…”
Section: Discussionsupporting
confidence: 72%
“…exposed to 25, 50, 75 and 100 Gy doses of gamma radiation. Salem, Fouda, Abas, Ali, and Gabarty (2014) demonstrated the decrease in the reproductive potential of Agrotis ipsilon when exposed to 50, 100, 150 Gy of gamma radiation.…”
Section: Discussionmentioning
confidence: 95%
“…Author(s) agree that this article remain permanently open access under the terms of the Creative Commons Attribution License 4.0 International License also reported that emergence of black cutworm at different radiation doses applied on egg stage decreases the hatching and induced sterility in adults, more over it prolong the larval and pupal stage of the insect (Salem et al, 2014). The objective of current is to evaluate the emergence of adult fruit flies by irradiating the pupae at different doses.…”
Section: Introductionmentioning
confidence: 96%